The effect of Expanding Maternal and Neonatal Survival interventions on improving the coverage of labor monitoring and complication prevention practices in hospitals in Indonesia: A difference‐in‐difference analysis. (27th February 2019) - Tholandi, Maya; Sethi, Reena; Pedrana, Alisa; Qomariyah, Situ Nurul; Amelia, Dwirani; Kaslam, Pancho; Sudirman, Sudirman; Apriatni, Mandri S.; Rahmanto, Agus; Emerson, Mark; Ahmed, Saifuddin
Abstract: Objective: To assess whether the Expanding Maternal and Neonatal Survival (EMAS) program was associated with improved care provided during hospital‐based childbirth. Methods: A quasi‐experimental study with two rounds of data collection examined whether EMAS interventions improved facility‐based labor and childbirth care. Direct clinical observations were conducted for 1208 deliveries across 13 hospitals in 12 districts. Primary outcome measures included implementation of standard practices to reduce the risk of complications during labor and childbirth for both women and newborns. Results: Adjusted difference‐in‐difference analysis compared the mean difference in quality scores between EMAS intervention hospitals and comparison sites and consistently found significantly better performance in EMAS sites: 14 points higher for labor monitoring (β‐coefficient 14.1; 95% confidence interval [CI], 7.1–21.0); 38 points higher for newborn resuscitation readiness (β‐coefficient 38.1; 95% CI, 31.1–45.2); and 33 points higher for infection prevention practices (β‐coefficient 32.6; 95% CI, 28.5–36.8). Conclusion: EMAS approaches emphasizing facility readiness and adherence to performance standards significantly improved labor monitoring and complication prevention practices during childbirth. Abstract : A quasi‐experimental pre/post assessment was conducted to assess labor monitoring, newborn resuscitation readiness, and infection prevention performance using clinical observations of labor and childbirth practices.